Tissue-infiltrating plasma cells are an important source of carboxylesterase 2 contributing to the therapeutic efficacy of prodrugs. Issue 1 (1st August 2016) - Kühl, Anja A.; Erben, Ulrike; Cieluch, Constanze; Spieckermann, Simone; Gröne, Jörn; Lohneis, Philipp; Pape, Ulrich Frank; Arsenic, Ruza; Utku, Nalân
Highlights: CES-2 protein levels in colorectal cancer in situ are not related to tumor grade. CES-2 high plasma cells are found in intestinal tissue of cancer and inflammation. In hepatocytes, CES-2 expression declines during tumorigenesis. Peripheral blood mononuclear cells of healthy donors express low levels of CES-2. Abstract: Carboxylesterase 2 (CES-2) is instrumental for conversion of ester-containing prodrugs in cancer treatment. CES-2 expression was analyzed by immunohistochemistry in colorectal cancer (CRC) compared to colonic inflammation as well as in liver and peripheral blood. In CRC, tumor grades showed no correlation with levels of CES-2 expression, which was heterogeneous within these tumors. Cellular infiltrates in the immediate tumor vicinity expressed high levels of CES-2. Thus, tissue adjacent to the tumor was a substantial source of CES-2 with high expression in plasma cells. CES-2 high plasma cells were abundantly found in the colon of patients with inflammatory bowel disease. CES-2 expression is strong in hepatocytes of normal livers, while CES-2 expression in peripheral blood mononuclear cells of healthy donors was overall low at protein and mRNA levels. In summary, the conversion of ester-containing prodrugs by CES-2 is mainly to occur in the periphery, during liver passage and in the colon after enterohepatic recirculation. We here demonstrated plasma cells as strong producers of CES-2. Further studies should elucidate the role of CES-2 + plasma cells in intestinal inflammation and cancer.